Implementation of Mayor Regulation No. 76 Of 2020 at Kalipancur State Elementary School 02 Concerning The Implementation Of Inclusive Education - Siswandari, Vanda Estetika; Suharini, Erni; Mulyono, Sungkowo Edy; Prihatin, Titi (Universitas Negeri Semarang, 2024)
The Semarang City Government has established Semarang Mayor Regulation No. 76 of 2020 concerning the Implementation of Inclusive Education as an effort to minimize accessibility limitations for Children with Special Needs in obtaining education. This research aims to analyze the implementation of inclusive education policies through Mayor regulation No.76 of 2020 at Kalipancur State Elementary School 02 Semarang city and the factors that influence the implementation process. The research method used is descriptive qualitative with data collection techniques, namely interviews and documentation. Implementation of Mayor regulation No.76 of 2020 at Kalipancur State Elementary School 02 Semarang city is seen from the dimensions of students, curriculum, educators, infrastructure, financing, role of community, guidance, control, supervision. In looking at the influencing factors, the theory of Mazmanian and Sabatier is used which consists of target groups, stakeholders, authorized bodies, implementing bodies. The implementation of inclusive education at Kalipancur State Elementary School 02 Semarang city has been running in accordance with existing regulations even though there are still obstacles in its implementation, as well as There are factors that hinder its implementation, namely differences in the economic types of parents/guardians of children with special needs, limited human resources at the Mental Revolution Ambassador's House (RDRM), limited budget from the Education Department, as well as limited knowledge and quantity of teachers for inclusive education students at Kalipancur State Elementary School 02 Semarang city.